Evaluation of Farmers Contentment with Climate Resilient Agricultureal Technologies in Telangana, India - Naik, Boda Mahesh; Maji, Saikat; Singh, A. K.; Venkatesan, P. (Current Science, 2024)
National Innovations on Climate Resilient Agriculture (NICRA) is a flagship project of the Indian Council of Agricultural Research (ICAR) to mitigate climate change in vulnerable districts of India. The present study assessed farmers$1 (Bsatisfaction with climate-resilient agricultural technologies following their adoption in two vulnerable districts of Telangana, India, identified under the NICRA project. Results showed that most farmers in the Suryapet and Khammam (62.67% and 90.00%) districts of Telangana state expressed high satisfaction with these technologies. Additionally, a significant proportion had a highly favourable perception of the technology promoters (71.33% and 82.00%), high perceived expectations (52.67% and 74.00%), high perceived quality (58.00% and 86.00%), and a high perceived value (68.00% and 84.00%) associated with climateresilient agricultural technologies. Importantly, the vast majority of the farmers in both districts expressed their intent to use these technologies when the need arises. Path analysis revealed that variables like perceived image, perceived expectation, perceived quality and perceived value had a significant direct impact on satisfaction, while there was no indirect effect on behavioural intention.s
Keywords: NICRA; Path analysisResilience; Technologies; Climate change